Decree-Law No. 54/2018 in vocational schools in Portugal: what challenges? (Revista Lusófona de Educação, 2025)
Decree-Law 54/2018 of 6 July opened the application of measures to support learning and inclusion,promoting equal opportunities and social equity, to vocational schools. However, and considering the specificities of vocational education, both in terms of students and the functioning of its subjects, the application ofthe regulations has been a challenge for teachers/trainers in these schools. In this sense, this quantitative studyseeks to understand the perception of teachers/trainers regarding the application of DL 54/2018 in vocationalschools, outlining the following objectives: to know the real difficulties experienced by teachers in applying thelaw; to understand whether, from the point of view of teachers/trainers in vocational schools, this regulation isappropriate to the reality of vocational education, taking into account certification at the end of the course; and toknow what the current challenges are for inclusive education in vocational schools. The results point to the needto provide schools with human resources capable of helping teachers to apply the measures; the respondentsrecognise the need for more training in the area and point out that the regulations are unsuited to the reality ofthis type of education, which confers professional certification.Keywords: Inclusion; vocational education; professional certification; teachers and trainers